2013
DOI: 10.5897/ajar10.411
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic evaluation of rice (Oryza sativa L.) for plant spacings and seedlings per hill under temperate conditions

Abstract: An experiment with rice as a test crop was conducted at the Experimental Farm, Shalimar Campus of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
2
3
1
1
Order By: Relevance
“…Shah et al, (1991) and H. Om et al, (1993), who reported that the plant height is significantly affected by the different planting geometry and found maximum plant height in closer plant spacing. These results are also accordance with Bezbaruha et al, (2011) and Rasool et al, (2013), who reported that closer plant spacing, produced tallest plant height than wider plant spacing in rice. Mahato and B.B.…”
Section: Resultssupporting
confidence: 82%
“…Shah et al, (1991) and H. Om et al, (1993), who reported that the plant height is significantly affected by the different planting geometry and found maximum plant height in closer plant spacing. These results are also accordance with Bezbaruha et al, (2011) and Rasool et al, (2013), who reported that closer plant spacing, produced tallest plant height than wider plant spacing in rice. Mahato and B.B.…”
Section: Resultssupporting
confidence: 82%
“…The application of ICW besides using NSV, the legowo planting method is one way to increase rice production. According to [40] reported that the legowo planting method is a method of planting rice by adjusting the spacing between clumps and between rows, resulting in compaction of the clumps and population per unit area. Meanwhile, according to [41] stated that the basic principle of how to plant legowo is to make all rows of plant clumps on the edge (border effect).…”
Section: Resultsmentioning
confidence: 99%
“…En consecuencia, algunas prácticas derivadas del SICA podrían ser estudiadas con mayor detalle a fin de diseñar sistemas más eficientes de producción de arroz. Estos sistemas, a su vez, podría facilitar la introducción de otras tecnologías, como por ejemplo, sistemas de siembra directa mecanizada, el uso de híbridos élite y la agricultura de conservación (ur Rasool et al, 2013;Wang et al, 2014).…”
Section: Resultados Y Discusiónunclassified